Tessier 30 facial cleft - Nirmal C Bhattacharyya; Kabita Kalita; Manoj Gogoi; Pradip K Deuri (Wolters Kluwer Medknow Publications, 2012)
A case of midline cleft of the lower lip with cleft of the mandible and complete duplication of the tongue is reported here. Median cleft of the lower lip, mandible and bifid tongue with ankyloglossia is reported in the literature, but complete duplication of the tongue as part of the Tessier 30 cleft is not yet reported.